The virus of syphilis in poetry: the case of Karyotakis - Menelaou, Iakovos (Research and Humanities in Medical Education, 2020)
Kostas Karyotakis (1896-1928) published three poetry collections: The Suffering of People and Things (1919), Nepenthe (1921) and Elegies and Satires (1927). A leading Greek poet, he influenced a significant number of poets, and this phenomenon became known as "Karyotakismos". Quite autobiographical, his poetry shows his agony, concerns and fears. The pessimistic atmosphere and the biographical elements the reader sees in Karyotakis' poems make his poetry distinct and it is still popular in our day. An important dimension of his poetry is the disease he had: syphilis. Karyotakis' syphilis has been discussed extensively, nevertheless none of the previous analyses attempted to read it through the lens of the medical humanities. Such a reading shows that apart from the biographical elements one may detect, there is a deeper meaning: the voice of an individual who experiences the disease at a time when there was no cure, syphilitics were stigmatised, and people treated them as outcasts. Karyotakis uses his poetry to share his personal tragedy and trauma. He is a syphilitic who wants his voice to be heard and his poems are valuable material as pathographies and for the study of the history of medicine.